The Role of Sports on the Development of Tribes Unity: Afghan Society, Kabul, Afghanistan - Bahir, Hizbullah (American International Journal of Social Science Research, 2020)
Sports play a major role in the life of humans as well as it has social and physical benefits for the humans’ body. The purpose of this research was to investigate the role of sports, relationships between nation and Afghan community, and its impacts on the development of Afghan people life. This study employed mixed research approach, and the data were collected from seventy-nine respondents through questionnaire and interview. All participants were elected through random sampling method, and the data was analyzed through IBM 24 version of (SPSS). Likewise, the findings of this research showed that sports play an essential role in Afghan community as well as it is inseparable part in their life. Moreover, men and women are very interested in participating sports. Furthermore, the study revealed that participation in sports and physical activities play a unique role on the development of Afghan community and tribes.